Measuring Progress towards Universal Health Coverage : With an Application to 24 Developing Countries - Wagstaff, Adam (World Bank, Washington, DC, 2015)
The last few years have seen a growing commitment worldwide to universal health coverage (UHC). Yet there is a lack of clarity on how to measure progress towards UHC. This paper proposes a ‘mashup’ index that captures both aspects of UHC: that everyone—irrespective of their ability-to-pay—gets the health services they need; and that nobody suffers undue financial hardship as a result of receiving care. Service coverage is broken down into prevention and treatment, and financial protection into impoverishment and catastrophic spending; nationally representative household survey data are used to adjust population averages to capture inequalities between the poor and better off; nonlinear tradeoffs are allowed between and within the two dimensions of the UHC index; and all indicators are expressed such that scores run from 0 to 100, and higher scores are better. In a sample of 24 countries for which there are detailed information on UHC-inspired reforms, a cluster of high-performing countries emerges with UHC scores of between 79 and 84 (Brazil, Colombia, Costa Rica, Mexico and South Africa) and a cluster of low-performing countries emerges with UHC scores in the range 35–57 (Ethiopia, Guatemala, India, Indonesia and Vietnam). Countries have mostly improved their UHC scores between the earliest and latest years for which there are data—by about 5 points on average; however, the improvement has come from increases in receipt of key health interventions, not from reductions in the incidence of out-of-pocket payments on welfare.